Learning-related fine-scale specificity imaged in motor cortex circuits of behaving mice - Komiyama, Takaki; Sato, Takashi R.; O’Connor, Daniel H.; Zhang, Ying-Xin; Huber, Daniel; Hooks, Bryan M.; Gabitto, Mariano; Svoboda, Karel (Nature (London), 2010)
Cortical circuits: learning to behave Although it is generally accepted that specific cortical circuits drive behavioural execution, the relationship between task performance and modulation within the circuit is unknown. Taking advantage of a technique that allows simultaneous activity monitoring of many neurons within the same circuit, Komiyama et al . imaged activity in two motor cortical areas in mice involved in the control of licking. In both areas there were cells that are preferentially excited in different trial types and predict different actions. These neurons were spatially intermingled. However, nearby neurons showed pronounced temporally coincident activity. These temporal correlations were particularly high for pairs of neurons with similar response types, and increased with learning. These correlations provide direct evidence for rapid changes in cortical microcircuits underlying flexible behaviour. It is generally accepted that specific neuronal circuits in the brain's cortex drive behavioural execution, but the relationship between the performance of a task and the function of a circuit is unknown. Here, this problem was tackled by using a technique that allows many neurons within the same circuit to be monitored simultaneously. The findings indicate that enhanced correlated activity in specific ensembles of neurons can identify and encode specific behavioural responses while a task is learned. Cortical neurons form specific circuits 1 , but the functional structure of this microarchitecture and its relation to behaviour are poorly understood. Two-photon calcium imaging can monitor activity of spatially defined neuronal ensembles in the mammalian cortex 2 , 3 , 4 , 5 . Here we applied this technique to the motor cortex of mice performing a choice behaviour. Head-fixed mice were trained to lick in response to one of two odours, and to withhold licking for the other odour 6 , 7 . Mice routinely showed significant learning within the first behavioural session and across sessions. Microstimulation 8 , 9 and trans-synaptic tracing 10 , 11 identified two non-overlapping candidate tongue motor cortical areas. Inactivating either area impaired voluntary licking. Imaging in layer 2/3 showed neurons with diverse response types in both areas. Activity in approximately half of the imaged neurons distinguished trial types associated with different actions. Many neurons showed modulation coinciding with or preceding the action, consistent with their involvement in motor control. Neurons with different response types were spatially intermingled. Nearby neurons (within ∼150 μm) showed pronounced coincident activity. These temporal correlations increased with learning within and across behavioural sessions, specifically for neuron pairs with similar response types. We propose that correlated activity in specific ensembles of functionally related neurons is a signature of learning-related circuit plasticity. Our findings reveal a fine-scale and dynamic organization of the frontal cortex that probably underlies flexible behaviour.